RENOVASI TEMPAT IBADAH DALAM UPAYA MENINGKATKAN KENYAMANAN BERIBADAH: Renovation of Places of Worship in an Effort to Increase the Comfort of Worship - Aminullah Aminullah; Hamid Hamid; Titin Apriani; Denianto Yoga Sativa; Dewi Asmawardhani; Titin Titawati; Arlina Maya Sari; Dedi Agustiawan (Yayasan Al-Amin Qalbu, 2026)
The physical comfort of a place of worship directly correlates with the reverence and tranquility of the congregation during worship activities. This community service project aims to make minor improvements to the prayer room (mushalla) on the campus of Universitas 45 Mataram. The method used to realize this community service activity is an active participation method with a descriptive approach. The implementation procedure includes the formation of a community service team, permitting, and implementing the service, which involves renovating the place of worship, or mushalla. The renovation of the mushalla as a form of community service begins with the formation of the team, obtaining permits, and implementing the service. The team consists of lecturers, educational staff, and students participating in the Community Service Program (KKN). The mushalla renovation is part of the KKN student program. Funding for the renovation comes from donors and volunteers within the team, not from the campus budget. The renovations include repairs to the roof, ceiling, doors, windows, and painting. The activity concludes with a cleanup and the installation of a signboard for the mushalla. The academic community, especially students, were very enthusiastic and moved by the renovation of the place of worship. This commitment was ultimately realized through self-funding, and the mushalla appears more comfortable for use as a place of worship.